Variations in macrobenthic community structure in relation to changing environmental conditions in sandy beaches of Argentina - Carcedo, Maria Cecilia (2015)
This study describes for the first time the intertidal macrobenthic community of exposed sandy beaches located near the Bahía Blanca Estuary (38°S) and reports the physical characterization of this coastal fringe. The main objective of the study was to link environmental variables to biotic information, analyzing the results in the context of the Swash Exclusion Hypothesis (SEH) and possible estuarine influence. Four beaches were sampled seasonally at different distances from the mouth of the Bahía Blanca Estuary. To characterize the morphodynamic state of the beaches, the Dean parameter (Ω) was calculated. Multivariate analyses were used to assess benthic community structures and their relationships with physical variables. The two beaches located closest to the Bahía Blanca Estuary were classified as intermediate and those located further from the estuary as dissipative. Richness, diversity and biomass of intertidal macrobenthic communities varied with the SEH, increasing towards the dissipative beaches. However, total density was higher on intermediate beaches, possibly because of nutrient-rich silt-clay sediment input from the estuary, enabling them to maintain a higher density of organisms than dissipative beaches. The estuary acts as a moderator of habitat hardness, which together with the morphodynamic state of the beaches is an important factor in the structuring of the macrobenthic community along this coastal fringe.